IMPLEMENTASI DIVERSI TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM (STUDI KASUS DI PULAU LOMBOK) - Rodliyah Joko Jumadi (Masalah-Masalah Hukum, 2013)
Abstract Diversion is a transfer juvenile settlement of the criminal justice process to the outside of the criminal justice process. The model was developed with the hope of resolving cases involving children, especially as criminals can involve stakeholders in society with emphasis on the restoration or recovery of the child victims and perpetrators. The focus of the issue raised in this study is how diversion program implementation in the handling of children in conflict with the law on the island of Lombok. Implementation of the Diversion has been conducted on the island of Lombok through diskresional police authority. In this implementation, although Diversion intended to protect children from the stigma and pressure of the judicial process, but in an indiscriminate diversion and not followed by action coaching the diversion and recovery will actually be threatening to the future of children. Key words : Children in conflict with the law, Diversion Abstrak Salah satu hal baru yang diatur dalam Undang-undang 11 tahun 2012 adalah Diversi. Diversi adalah  pengalihan penyelesaian perkara Anak dari proses peradilan pidana ke proses di luar peradilan pidana. Fokus permasalahan yang diangkat dalam penelitian ini adalah Bagaimanakah implementasi program Diversi dalam  penanganan anak yang berhadapan dengan hukum di pulau lombok. Hasil penelitian menunjukan bahwa Diversi telah dilaksanakan di pulau Lombok  melalui kewenangan diskresional kepolisian. Dalam implementasinya meskipun Diversi ditujukan untuk melindungi anak dari stigmatisasi dan tekanan proses peradilan namun apabila diversi dilakukan secara serampangan  dan tidak diikuti dengan tindakan pembinaan dan pemulihan maka diversi malah akan menjadi pengancam bagi masa depan anak.   Kata Kunci : Anak Berhadapan dengan Hukum, Diversi